2003
DOI: 10.1258/002221503322112950
|View full text |Cite
|
Sign up to set email alerts
|

Consent processes in common nose and throat procedures

Abstract: The NHS Plan identified the need for changes in consent practice, and led to the issuing of a model consent policy and standard consent forms for use in the NHS. The aim of this study was to determine current consent practices for common rhinology and laryngology procedures. A telephone survey was conducted of 40 otolaryngology Senior House Officers (SHOs) across England and Wales, asking about local consent procedure, and the specific complications discussed before common operations. The responsibility for ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…They suggest that consent should be obtained by senior staff, in a controlled environment. Many departments have responded to this by consenting in outpatients 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…They suggest that consent should be obtained by senior staff, in a controlled environment. Many departments have responded to this by consenting in outpatients 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…Increase in the awareness of different websites has increased nonmedical sourcing of information being utilized by patients [5]. In this era of increased patient expectations, the medical profession is trying to optimize information delivery by using patient decision software [6] and printed information sheets (in up to 25% of ENT departments) [7] and increasingly by shifting the role of provision of patient information to more senior members of the team [8, 9]. Some studies in the United States have argued that the federal government poses an actual barrier to informed consent concerning oral contraceptives and induced abortion [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to Chadha and colleagues' 2002 survey, model NHS consent forms were used in 72.5 per cent of departments, and information sheets given to patients in just 25 per cent. 4 A follow-up study by McDonald et al in 2005, with matched methodology, showed a reduction in routine consenting by SHOs (to 82 per cent; p ¼ 0.2), an increase in the use of standardised NHS consent forms (to 77.5 per cent; p ¼ 0.4) and a significant improvement in the use of information sheets (to 57.5 per cent; p ¼ 0.0002), since the 2002 study. 5 There were perceptible and occasionally significant reductions in the incidence of SHOs undertaking routine consenting for five of the most common ENT procedures, representing a probable shift towards the recommended practice of consent being obtained by senior members of the surgical team (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The study also aimed to identify any shifts in practice which may relate to recent changes in junior doctor training and service provision. 4,5 Methods A telephone questionnaire of SHOs working in 40 randomly-selected UK ENT departments was conducted during December 2008, using the same departments and methodology as previously published. 4 A 100 per cent participation rate was achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation